Stretching after an in-water warm-up does not acutely improve sprint freestyle swim performance in DIII collegiate swimmers - Westra, H. L.; Montoye, A. H. K. (Topics in Exercise Science and Kinesiology, 2021)
Topics in Exercise Science and Kinesiology Volume 2: Issue 1, Article 11, 2021. Stretching, as part of a warm-up prior to competition, has been used as a method to enhance performance in swimming and other sports, but its efficacy as a potential ergogenic aid remains understudied. This study`s purpose was to determine if acute static stretching or a dynamic warm-up, following an in-water swim-specific warm-up, improved sprint freestyle swim performance in collegiate swimmers. NCAA Division III swimmers (n=15, 67% female) participated in three testing protocols. In each protocol, participants did an in-water warm up and either a dynamic warmup (DW), static stretching warmup (SS), or no stretching (CON) routine followed by three, 100-yard freestyle sprints, each performed four minutes apart. Swim times were recorded for the first and second 50-yard splits and for the full 100 yards in each trial. Repeated-measures analysis of variance and effect sizes were used to assess differences across protocols. Average performance was significantly faster for CON compared to DW for the first 50-yard split (mean difference ~0.47 seconds, p=0.044) and total 100-yard time (mean difference ~0.77 seconds, p=0.017), with medium effect sizes for both. No differences were observed between SS and the other protocols. Adding acute stretching or dynamic warm-up, following an in-water warm-up, either did not improve or was associated with poorer 100-yard freestyle swim performance than solely performing an in-water warm-up. Swimmers should carefully evaluate their warm-up routines and consider a focus on in-water warm-ups for maximizing sprint swim performance.